Gambling addiction: myth or reality? Analysing the scientific evidence on gambling disorder. - Gemma Mestre-Bach (Mètode Science Studies Journal, 2022)
Interest in gambling disorder, formerly known as pathological gambling, has been growing in both the clinical and scientific community. The increase in empirical evidence concerning gambling disorder has permitted a better understanding of the pathology, as well as the identification of common comorbidities and the design of potential therapeutic options. The present review addresses all these issues, including recent findings in this area of study.